Consider the equation: x 2 − 6 = 2 − 18 x x 2 −6=2−18xx, squared, minus, 6, equals, 2, minus, 18, x 1) Rewrite the equation by completing the square. Your equation should look like ( x + c ) 2 = d (x+c) 2 =dleft parenthesis, x, plus, c, right parenthesis, squared, equals, d or ( x − c ) 2 = d (x−c) 2 =dleft parenthesis, x, minus, c, right parenthesis, squared, equals, d. 2) What are the solutions to the equation? Choose 1 answer: Choose 1 answer: (Choice A) A x = 9 ± 89 x=9±89x, equals, 9, plus minus, 89 (Choice B) B x = − 9 ± 89 x=−9±89x, equals, minus, 9, plus minus, 89 (Choice C) C x = 9 ± 89 x=9± 89 ​ x, equals, 9, plus minus, square root of, 89, end square root (Choice D) D x = − 9 ± 89 x=−9± 89 ​ x, equals, minus, 9, plus minus, square root of, 89, end square root

Respuesta :

Answer:

1. (x+9)^2 = 89

2. (Choice D) D x = − 9 ± 89 x=−9± 89 ​ x, equals, minus, 9, plus minus, square root of, 89, end square root

Step-by-step explanation:

x^2 - 6 = 2 - 18x

1) rewrite the equation by completing the square

x^2 - 6 = 2 - 18x

x^2 + 18x = 2+6

x^2 + 18x = 8

Find the half of the coefficient of x and square it

18x

Half=9

Square half=(9)^2

=81

Add 81 to both sides

x^2 + 18x = 8

x^2 + 18x + 81 = 8 + 81

x^2 + 18x + 81 = 89

(x+9)^2 = 89

Check:

(x+9)(x+9)=89

x^2 + 9x + 9x + 81=89

x^2 + 18x +81 =89

2) (x+9)^2 = 89

√(x+9)^2 = √89

x+9=√89

x=√89 - 9

It can be rewritten as

x= -9 ± √89

(Choice D) D x = − 9 ± 89 x=−9± 89 ​ x, equals, minus, 9, plus minus, square root of, 89, end square root